2014
DOI: 10.1038/ejhg.2014.244
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis in intestinal mucosa reveals complex relations among genes under the association peaks in celiac disease

Abstract: Celiac disease is a chronic immune-mediated disorder with an important genetic component. To date, there are 57 independent association signals from 39 non-HLA loci, and a total of 66 candidate genes have been proposed. We aimed to scrutinize the functional implication of 45 of those genes by analyzing their expression in the disease tissue of celiac patients (at diagnosis/treatment) compared with non-celiac controls. Moreover, we investigated the SNP genotype effect in gene expression and performed coexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 20 publications
(23 reference statements)
4
29
0
Order By: Relevance
“…In this study, 44 SNPs and 45 candidate genes were investigated, which resulted in four cis-eQTL as well as multiple CeD SNPs that affected the expression of genes far away (often on other chromosomes, socalled trans-eQTLs). In agreement with the other studies mentioned above, they also found some stimulus-dependent eQTLs [36]. To obtain a full picture, more eQTL studies need to be done in diseasespecific tissues and under different conditions, in order to prioritize the candidate genes from the associated loci.…”
Section: The Majority Of Ced Snps Map To Regulatory Variationssupporting
confidence: 74%
See 2 more Smart Citations
“…In this study, 44 SNPs and 45 candidate genes were investigated, which resulted in four cis-eQTL as well as multiple CeD SNPs that affected the expression of genes far away (often on other chromosomes, socalled trans-eQTLs). In agreement with the other studies mentioned above, they also found some stimulus-dependent eQTLs [36]. To obtain a full picture, more eQTL studies need to be done in diseasespecific tissues and under different conditions, in order to prioritize the candidate genes from the associated loci.…”
Section: The Majority Of Ced Snps Map To Regulatory Variationssupporting
confidence: 74%
“…This lncRNA is strongly expressed in CD8 þ T-cells and is suggested to function in alphaebeta T-cell proliferation and B-cell activation, both of which are crucial processes in autoimmunity. AC104820.2 was also found to be up-regulated in the intestinal biopsies of patients with active CeD, further confirming its role in the disease [36]. MiRNAs are also recognized as important in CeD.…”
Section: Non-coding Rnas and Cedmentioning
confidence: 74%
See 1 more Smart Citation
“…In a preliminary study, Plaza-Izurieta et al performed cis e-QTL analyses in 8 GWAS-associated regions and found significant results for IL12A, LPP, SCHIP1 and SH2B3 [119]. In a subsequent work, these authors extended the analyses to 45 genes under association peaks in CD [70] and found 15 genes differentially expressed between active CD patients and non-celiac controls, and 11 between active and treated CD. Gene expression was found to be influenced by the genotype at several SNPs in a stimulus-dependent manner and, strikingly, most e-QTLs were in trans, i.e., SNPs affected the expression of distant genes.…”
Section: Insights From Non-mhc Genetic Variantsmentioning
confidence: 92%
“…Interestingly, lincRNA expression seems to be more tissue-dependent than protein-coding genes [68] and is influenced by individual genotypes, being many lincRNA ciseQTL SNPs associated with complex traits and diseases [69]. No studies specifically focused on lincRNAs have been performed in relation to CD, but Plaza-Izurieta et al found that one SNP significantly associated with CD risk (rs1018326) maps to a lincRNA of unknown function (AC104820.2) [70]. The expression of AC104820.2 seemed to be higher in active disease.…”
Section: Epigeneticsmentioning
confidence: 95%